Basmacı İsyanı ve Sovyet-Afgan Sınır Anlaşmazlığı (1925-1926) - Mehmet Erkan KILLIOĞLU (Gazi Akademik Bakış)
Afghanistan, bordering the Turkestan, has a priority in the foreign policy of the Tsarist Russia and the Soviet Union. During the 19th century, Afghanistan witnessed the struggle for influence between Tsarist Russia and England. The parties agreed that Afghanistan should be a buffer zone so that this competition, called the Great Game, does not cause irreparable damage. However, the events experienced during this rivalry increased the sensitivity of Tsarist Russia against attacks from Turkistan and Kazakh Steppe in the south due to the absence of geographical barriers. Tsarist Russia left this legacy to its successor, the USSR. After the 1917 October Revolution, the Bolshevik administration in Turkestan was not accepted by the local population. A rebellion movement broke out against the Bolshevik administration, which was seen as an obstacle to the independence of the region. The Soviets, who did not want to lose Turkistan tried to end the Basmacı Rebellion quickly. During this revolt, the Basmachi’s attacked the Soviet targets in Turkestan and returned to Afghanistan after these attacks. For the Soviets ending this freedom movement was the primary goal. Therefore, the control of the border between the two countries has gained importance. However, due to the summer drought, the drying up of the Ceyhun and Penc Rivers and the merger of the Urtha Tugai Island on the Afghan coast made this control difficult. A serious crisis has emerged between the two countries. For the solution of the crisis, the Soviet’s asked Afghan State to end her support to Basmachis